Libro de embeźar las linguas ingleśa y yudiš: La América’s Guidebook to Learning English and Yiddish and Becoming an American Citizen - Scolnik, Julie L (Miscelánea de Estudios Árabes y Hebraicos. Sección Hebreo, 2014)
This article is the study of a book published by the Sephardic newspaper La América so that the Sephardic immigrants in the United States could learn English and Yiddish and thus better adapt to their life in the new country and even prosper. Its editor, Moise Gadol endeavored to make emmigrating to the United States easier which is why the newspaper was distributed not only in the United States but also in cities of the Ottoman Empire. The book includes chapters on immigration, the law of immigration in effect at the time, warning the readers of the possible reasons for being denied entry, and the questions and answers of the exam to become a U.S. citizen. The last part is a method to learn English and Yiddish which consists of twenty-four pages of vocabulary and twenty-four pages of conversation, all of which is aljamiado, English included.